Local Wisdom and Product Competition Model of MSMEs Rambutan Tangkue Based on Intellectual Property In Curugbitung Sub-District, Lebak District - Sulasno, Sulasno; Rifai, Ahmad; Rostiyana, Ayu (Green Publisher Indonesia, 2024)
Local wisdom is a view of life and also knowledge in which there are various life strategies which have a form of activity carried out by local communities which certainly helps to answer various problems, especially in meeting community needs. This research aims to determine the competition model in selling products for micro, small and medium enterprises in rambutan tangkue fruit, as well as to determine the concept of developing local wisdom (local wisdom), especially in micro, small and medium enterprise products for rambutan tangkue in Curugbitung District, Lebak Regency. This research uses qualitative methods with an empirical juridical approach. The data used includes primary data, secondary data and tertiary data. This research shows that the competition model for MSMEs rambutan tangkue products in Curugbitung District usually prioritizes cooperation with each other in achieving profits and superiority of rambutan tangkue fruit and the concept of developing local wisdom of rambutan tangkue fruit using the concept of production response, innovation-friendly processes and marketing strategies creative one.